Pengembangan Media Pembelajaran Video Animasi Mata Pelajaran IPAS Kelas IV SD - Tilayah, Reski; Nuranisa; Etty Pratiwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop animated video-based learning media for the IPAS subject on the topic “Me and My Needs” for fourth-grade elementary school students that is valid and practical for use in learning. This research employs a Research and Development (R&D) method using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. Data collection techniques used in this study include validation sheets, questionnaires, and documentation. The results show that the developed learning media obtained a validity score of 89.64%, categorized as very valid, and a practicality score of 87.6%, categorized as very practical. Therefore, the animated video-based learning media is considered valid and practical for use in the learning process.